Formulasi Granul Effervescent Ekstrak Etanol Buah Gowok - Dewi Fitriani Puspitasari (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Harapan Bersama, 2022)
Kupa or gowok fruit is a fruit that contains anthocyanin compounds, which have potential as antioxidants. Fruit with a fresh sweet and sour taste can be utilized by being formulated into effervescent granules that are practical and have a good taste. The purpose of this study was to formulate the effervescent granule preparation of gowok fruit. Gowok fruit extraction using maceration method with ethanol solvent, then making effervescent granules using wet granulation method and evaluation includes organoleptic, MC, BJ tests, flow properties and dissolving time. The results of the formulations showed that the three granule formulas met the results of the physical characteristics test.